LEGAL PROTECTION FOR COPYRIGHT OF SONGS ON THE INTERNET - Chrisna Arwiandra Leuwol; Mohammad Saleh (INFOKUM, 2023)
The development of advanced technology and faster, ease of accessing the virtual world leads to equal public access to information collected on the internet, one of which is a song, a recording of rhythmic sound that was originally shaped physically from the record vinyl then began to become a tape cassette for radio tape and now evolved along with technology into intangible that is digital in the world of internet and digital storage media like DVD, Flash disk, and Hard disk. The Internet connects the global world to a single location. Based on this case KEMENKOMINFO (Ministry of Communication and Informatics) has attempted to enforce the closure of a number of sites that commit illegal acts such as uploading, downloading and reproduction and reproduction of songs on the internet without the permission of the creator and copyright holder. From the problematic law is written this thesis about copyright protection of songs on the internet, what the copyright standards of songs on the internet along with the form of copyright infringement of songs on the internet and recovery efforts